2014
DOI: 10.1089/aid.2013.0251
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Intervention to Reduce Intravaginal Practices Among HIV-1 Uninfected Kenyan Women

Abstract: Intravaginal practices (IVP) are common among African women and are associated with HIV acquisition. A behavioral intervention to reduce IVP is a potential new HIV risk-reduction strategy. Fifty-eight HIV-1-uninfected Kenyan women reporting IVP and 42 women who denied IVP were followed for 3 months. Women using IVP attended a skill-building, theory-based group intervention occurring weekly for 3 weeks to encourage IVP cessation. Vaginal swabs at each visit were used to detect yeast, to detect bacterial vaginos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 28 publications
(27 reference statements)
0
23
0
Order By: Relevance
“…Our intervention study provides advancement over previous studies as our comprehensive approach included: 1) multiple methods to assess the VM (Amsel criteria, Nugent scoring and 16 s rRNA gene sequencing); 2) a standardized intervention (all participants used the same douching product and used it with similar frequency); 3) sampling before, during and after douching product use; 4) more frequent sampling than previously reported; and 5) data on potential confounders such as sexual intercourse and menses. Douching cessation was previously studied prospectively, and these studies did not detect an overall effect on the VM composition [9, 22, 24], except for women who primarily douched to cleanse after menses [9]. However, these studies relied on self-reported douching events and participants within the same study populations did not all douche with the same product and/or frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Our intervention study provides advancement over previous studies as our comprehensive approach included: 1) multiple methods to assess the VM (Amsel criteria, Nugent scoring and 16 s rRNA gene sequencing); 2) a standardized intervention (all participants used the same douching product and used it with similar frequency); 3) sampling before, during and after douching product use; 4) more frequent sampling than previously reported; and 5) data on potential confounders such as sexual intercourse and menses. Douching cessation was previously studied prospectively, and these studies did not detect an overall effect on the VM composition [9, 22, 24], except for women who primarily douched to cleanse after menses [9]. However, these studies relied on self-reported douching events and participants within the same study populations did not all douche with the same product and/or frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Vaginal washing is common worldwide, and is motivated by perceptions of cleanliness and hygiene [13]. Methods of vaginal washing vary greatly across different regions.…”
Section: Introductionmentioning
confidence: 99%
“…Responses suggest that the promotion of tightening cessation in a prevention program would not pose an issue, as adolescents and young adults understand the health impacts associated with IVPs. In a previous study, Sivapalasingam et al implemented a behavioral intervention to reduce IVP use among HIV-1 uninfected Kenyan women and found that group counseling was effective in reducing IVPs for 3 months 20. However, the majority of the couples in the present study appreciated the use of focus groups and claimed that focus groups would provide a safe environment to gather, discuss, and learn things that could help their relationships.…”
Section: Discussionmentioning
confidence: 56%